Fourth root prescription for dynamical staggered fermions - Adams, David H. (2013)
With the aim of resolving theoretical issues associated with the fourth root prescription for dynamical staggered fermions in lattice QCD simulations, we consider the problem of finding a viable lattice Dirac operator D such that (detD staggered ) 1/4 =detD . Working in the flavor field representation we show that in the free field case there is a simple and natural candidate D satisfying this relation, and we show that it has acceptable locality behavior: exponentially local with a localization range vanishing ∼√ a/m for lattice spacing a→0 . Prospects for the interacting case are also discussed, although we do not solve this case here.